Degenerative meniscus tears - assimilation of evidence and consensus statements across three continents: state of the art. Issue 2 (21st April 2017) - Stone, Jonathan A; Salzler, Matthew J; Parker, David A; Becker, Roland; Harner, Christopher D
Abstract : Arthroscopic partial meniscectomy has been considered a gold standard treatment for meniscal tears for the past three decades, which has led to partial meniscectomy being the most commonly performed orthopaedic procedure in countries across three continents. Because of the prevalence of meniscal tears, there is a tremendous impact of their 'simple' surgical management on the world's population. The management of degenerative meniscal tears has been changing due to numerous level I studies. While the majority of these studies find little difference between conservative management and partial meniscectomy, these studies have multiple exclusions and high cross-over rates from the non-surgical to the surgical groups. We present a review of the evidence and consensus statements from multiple continents on the treatment of degenerative meniscal tears.